Antidandruff Activity of Extracts From Kaffir Lime (Citrus Hystrix Dc.) Prepared By Different Solvents - Lisawati Tanzil; Latirah Latirah; Priyanto Dwi Nugroho (Politeknik Kesehatan Kemenkes Jakarta II, 2017)
Pytiriasiscapitis or dandruff is a condition of exofoliate peeling of the stratum corneum layer in the scalp. There are some factors that suspected to caused dandruff such as increased production of sebum, sensitivity individual against the sebum and microbiota activity in scalp, i.eMalasseziafurfur, Malassezia globosa, Pytirosporumovale, and Candida albicans. Therefore, treatment of dandruff is aimed to reduced sebum on the scalp and inhibit the growth of yeast population that causes dandruff. The juice of kaffir lime fruit (Citrus hystrix DC.) has been used by Indonesian people for tradisional therapy of dandruff. This study thas been conducted to find out antidandruff activities of M. furfur from kaffir lime fruit juice, peel, and leaves of kaffir lime tree extracted by ethanol, ethyl acetat, and n-hexan solvents. Antifungal activitiesis measured by inhibition zones using well diffusion agar methods.All citrus extracts showed antifungal activities against M. furfur with ethyl acetat solvent indicated the highest antidandruff activities, then followed by n-hexan, and ethanolicsolvent; although ethyl acetat and n-hexan was not significantly different (p>0.05).Leaves extract showed highest inhibition activities, then followed by fruit juice and peel extract, although leaves and fruit juice extracts was not significantly different (p>0.05).Part of the plant citrus consist of a alkaloid, saponin, tannin, phenolic, flavonoid, terpenoid, glikosida, and steroid. Antifungal activities suspected of phenolic, flavonoid, and terpenoid compounds. These results suggested that kaffir lime are effective against dandruff microbial and has potential as a herbal shampoo for dandruff treatment.